EFFECTIVENESS OF A PROPOSED REHABILITATION PROGRAM FOR MEDIAL TIBIAL STRESS SYNDROME AND ITS IMPACT ON PAIN LEVELS AND PHYSICAL ABILITIES IN ATHLETES - Asst.prof.doc Ali Awad Jabbar (Proximus Journal Publishing, 2024)
This study aimed to evaluate the effectiveness of a proposed rehabilitation program for treating medial tibial stress syndrome in athletes, focusing on its impact on pain reduction and the improvement of selected physical abilities. The study included a sample of seven athletes diagnosed with medial tibial stress syndrome who underwent the proposed rehabilitation program. The program lasted for eight weeks, with three sessions per week. Pain levels were measured using the Visual Analog Scale (VAS), and selected physical abilities (muscle strength and electromyography) were assessed before and after the implementation of the program. The results showed a significant decrease in pain levels among the study participants. The study concluded that the proposed rehabilitation program is effective in alleviating pain and enhancing selected physical abilities in athletes suffering from medial tibial stress syndrome. The study recommends adopting this program as part of treatment protocols for this injury and suggests further research to evaluate its long-term effects on athletic performance and the prevention of recurrence
Keywords: prevention; effects; performance; recurrence